Raw physical oceanography and current meter data from mooring 79N6-2 in the Greenland Sea, September 2018 - September 2021 - Mario Hoppmann; Rebecca McPherson; Ulrich Drübbisch; Cassandra Elmer; Carina Engicht; Stylianos Kritsotalakis; David Kulmey; Matthias Monsees; Andreas Münchow; Torsten Kanzow (PANGAEA, 2024)
Time-series data of physical oceanography and ocean current velocities were obtained from mooring 79N6-2 in the Greenland Sea close to the 79 North Glacier between September 2018 and September 2021. The mooring was deployed during RV Maria S. Merian expedition MSM76, and recovered during Danish coast guard patrol vessel HDMS Triton expedition TRITON2021. The attached archive contains raw data files of two Seabird SBE37 MicroCATs (nominal depths: 189m, 254m; sampling interval 20min), three SBE56 temperature logger (nominal depths: 154m, 219m, 254m; sampling interval 30s), one SBE16 SeaCAT (nominal depth: 115m; sampling interval 1h), and one RDI Quartermaster ADCP (nominal depth: 254m; sampling interval 1h). Auxiliary information such as sensor calibration sheets, protocols, mooring diagrams, and schedule files are also provided, if applicable.
In: Hoppmann, Mario (2026): Collection of raw data from oceanographic moorings in the Fram Strait, Greenland Sea, and central Arctic Ocean, 2018-2025 [dataset publication series]. PANGAEA, https://doi.pangaea.de/10.1594/PANGAEA.959812 (DOI registration in progress)